Pengaruh Iklan di Media Sosial dan Komunikasi Word of Mouth Terhadap Keputusan Pembelian Konsumen Pada PT Berkah Jaya Medan - Anggia Sari Lubis (Forum Kerjasama Pendidikan Tinggi, 2020)
The use of the internet in the current era of globalization has become a priority for every individual as a means of finding various information needed quickly and up to date. Social media users have also increased greatly. It is also PT Berkah Jaya Medan's choice to advertise its products through social media. In social media advertising, consumers usually give testimonials which are known as word of mouth communication so that the objectives of the sales target can be achieved. Based on these problems, the objectives of this study are: (1) to determine the effect of advertising on social media on consumer purchasing decisions of PT Berkah Jaya Medan, (2) to determine the effect of word of mouth communication on consumer purchasing decisions of PT Berkah Jaya Medan, and ( 3) to determine the effect of advertising on social media and word of mouth communication on consumer purchasing decisions of PT Berkah Jaya Medan. The population used in this study were 208 consumers of PT Berkah Jaya Medan each week. The sample in this study was 68. Sampling was using the Slovin formula. The data in this study used a survey method through questionnaires filled out by consumers. Data were obtained using multiple regression analysis. This analysis includes the validity test, reliability test, classic assumption test, multiple regression analysis, hypothesis testing through the t test and F test, and analysis of the coefficient of determination (R2). From the regression analysis obtained the following equation, Y = 2.375 + 0.294 X1 + 0.671 X2 + e. The word of mouth variable has a greater influence on consumer purchasing decisions, namely 0.671, followed by social media advertising variables of 0.294. The results of the analysis using the t test can be seen that the two independent variables, namely advertising in social media, word of mouth partially have a significant effect on the dependent variable, namely consumer purchasing decisions. Then through the F test it can be seen that the two independent variables are indeed feasible to test the dependent variable. The value of Adjusted R Square is 0.849, which means that the variable ability of social media advertising, word of mouth in explaining consumer purchasing decisions is 84.9%, so there is still a residual of 15.1% requiring other variables not researched.